Long lasting MDM2/Translocator protein modulator: a new strategy for irreversible apoptosis of human glioblastoma cells - Daniele, Simona (Oncotarget, 2016)
The development of multi-target drugs and irreversible modulators of deregulated signalling proteins is the major challenge for improving glioblastoma multiforme (GBM) treatment. Reversible single-target drugs are not sufficient to sustain a therapeutic effect over time and may favour the activation of alternative signalling pathways and the onset of resistance phenomena. Thus, a multi-target compound that has a long-lasting mechanism of action might have a greater and longer life span of anti-proliferative activity. Recently, a dual-target indol-3ylglyoxyldipeptide derivative, designed to bind to the Translocator Protein (TSPO) and reactivate p53 function via dissociation from its physiological inhibitor, murine double minute 2 (MDM2), has been developed as a potent GBM pro-apoptotic agent. In this study, this derivative was chemically modified to irreversibly bind MDM2 and TSPO. The new compound elicited a TSPO-mediated mitochondrial membrane dissipation and restored p53 activity, triggering a long-lasting apoptosis of GBM cells. These effects were sustained over time, involved a stable activation of extracellular signal regulated kinases and were specifically observed in cancer cells, in which these protein kinases are deregulated. Dual-targeting and irreversible binding properties combined in the same molecule may represent a useful strategy to overcome the time-limited effects elicited by classical chemotherapies.